Antimicrobial peptide plasma concentrations in patients with community-acquired pneumonia. (June 2013) - Jendeberg, Anna Lange; Strålin, Kristoffer; Hultgren, Olof
Abstract Background: Community-acquired pneumonia (CAP) is a common and potentially life-threatening infection. Innate immunity is the first line of defence, and antimicrobial peptides (AMPs) produced by white blood cells and at epithelial barriers participate by killing microorganisms and neutralizing bacterial toxins. We wanted to investigate whether concentrations of AMPs (1) are increased in CAP, (2) predict the clinical outcome, and (3) differ depending on the causative microbe. Methods: Plasma concentrations of AMPs were measured using an enzyme-linked immunosorbent assay in 89 patients with CAP, 21 patients with non-respiratory tract infections (non-RTI), and 63 healthy control subjects. Results: In subjects with CAP, mean plasma concentrations of secretory leukocyte protease inhibitor (SLPI) and bactericidal/ permeability-increasing protein (BPI) were significantly higher than in healthy control subjects (85 vs 45 ng/ml, p < 0.001 and 48 vs 10 ng/ml, p < 0.001, respectively), but less markedly increased in patients with non-RTI (68 ng/ml, p = 0.06 and 41 ng/ml, p = 0.43). LL-37 and human neutrophil peptides 1–3 (HNP 1–3) levels were not increased in subjects with CAP. Levels of BPI and SLPI did not correlate to severity of disease, and AMP levels did not differ depending on the causative agent. Interestingly, male subjects with CAP displayed increased concentrations of SLPI compared to females. This was not observed in subjects with non-RTI and healthy control subjects. Conclusions: Subjects with CAP showed increased plasma concentrations of SLPI and BPI compared to healthy control subjects. The finding of higher SLPI levels in male subjects with CAP implies that there are sex-dependent immunological differences in SLPI turnover.